2018
DOI: 10.1039/c7cy02014g
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent catalytic performance of ruthenium nanoparticles in the hydrogenolysis of a β-O-4 lignin model compound

Abstract: One-pot depolymerization of lignin to well-defined chemicals and their further deoxygenation to arenes are extremely attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…Herein, the Ru NP size of Ru@C–DP was distinctly smaller than that of Ru@C‐EG and Ru@C–IM, but the catalytic activity and selectivity of the former was definitely much better than that of the two latter ones, suggesting a size‐dependent effect in the catalytic aromatic hydrogenation performance of the Ru@C catalysts. The similar phenomenon was also observed in lignin hydrogenolysis, CO methanation and oxidation as well as ammonia synthesis over the Ruthenium‐based catalysts . For example, Dong et al.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Herein, the Ru NP size of Ru@C–DP was distinctly smaller than that of Ru@C‐EG and Ru@C–IM, but the catalytic activity and selectivity of the former was definitely much better than that of the two latter ones, suggesting a size‐dependent effect in the catalytic aromatic hydrogenation performance of the Ru@C catalysts. The similar phenomenon was also observed in lignin hydrogenolysis, CO methanation and oxidation as well as ammonia synthesis over the Ruthenium‐based catalysts . For example, Dong et al.…”
Section: Discussionsupporting
confidence: 66%
“…found that the catalytic activities and the product distributions in lignin hydrogenolysis strongly depended on the size of Ru nanoparticles (NPs). Specifically, Ru NPs with smaller size (1.2 and 1.8 nm) exhibited a higher activity for the cleavage of C–O bond, whereas Ru NPs with larger size (2.5 and 5.3 nm) showed a much lower activity . Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The adsorption and binding of phenol molecules on the Nb 2 O 5 (001), ZrO 2 (010), Al 2 O 3 (110), and TiO 2 (101) surfaces further confirm that, among these oxides, Nb 2 O 5 has strong adsorption of phenol and low disassociation energy of C aromatic −OH bonds (Figure ) . Subsequent investigations, including those of metal size effects, electronic effects, and Nb 2 O 5 surface properties, revolved around the activation of the phenolic hydroxy groups over Nb‐based catalysts . As previously mentioned, the size of the Ru nanoparticles strongly affects the lignin hydrogenolysis activities and product distributions .…”
Section: Upgrading Of Lignin‐derived Monomersmentioning
confidence: 99%
“…The Ru‐colloid loaded Nb‐based catalysts with the same Ru particles were prepared by adsorption of colloidal Ru nanoparticles (NPs) onto the Nb 2 O 5 −L, Nb 2 O 5 −H and Nb 2 O 5 −F supports . Colloidal Ru NPs with size of 1.2 nm was prepared through the reduction of RuCl 3 with ascorbic acid in the aqueous phase 80 °C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…The Ru-colloid loaded Nb-based catalysts with the same Ru particles were prepared by adsorption of colloidal Ru nanoparticles (NPs) onto the Nb 2 O 5 À L, Nb 2 O 5 À H and Nb 2 O 5 À F supports. [22] Colloidal Ru NPs with size of 1.2 nm was prepared through the reduction of RuCl 3 with ascorbic acid in the aqueous phase 80°C for 1 min. Then, add the support into the colloidal Ru particle solution and stirred for 24 h. Finally, it was washed by DI water and dried at 50°C vacuum oven.…”
Section: Catalyst Preparationmentioning
confidence: 99%